Role of the support on the performance and stability of Pt-based catalysts for furfural–acetone adduct hydrodeoxygenation. Issue 3 (2nd December 2014) - Faba, L.; Díaz, E.; Ordóñez, S.
Abstract : The roles of metal dispersion and support properties of Pt catalysts on their performance for HDO of condensation adducts have been determined. Abstract : The role of the support on the catalytic activity, product distribution, and stability of supported Pt catalysts in the hydrodeoxygenation of an acetone–furfural condensation adduct is studied in the present work. Supports such as ZSM-5, L and Y zeolites, high surface area graphites and activated carbons have been tested, modelling the results after a previously proposed reaction network. The analysis of the kinetic constants shows that the first steps (hydrogenation of aliphatic multiple bonds) are structure sensitive, mostly depending on metal dispersion, whereas those steps involving ring opening and HDO of the resulting diols present a more complex chemistry, involving the morphological and acid–base properties of the support. Concerning the catalyst stability, the formation of carbonaceous deposits is the main deactivation cause.